Market Concentration and X-efficiency in Indian Commercial Banking System - Hong, Yanting (2014)
The face of the Indian banking system has been impressively changed with the employment of the new technologies and the reform mainly in 1991. Some measures such as deregulation, low the entry barriers aims at improving the flexibility, competition and efficiency in Indian banking system, and eventually, help the government achieve their economic and social goals. The purpose of this study is to analyze the relationship among the market structure, efficiency and profitability. Efficiency scores that are related with the x-efficiency like cost efficiency, allcoative efficiency, technical efficiency, pure technical efficiency and scale efficiency are obtained from both the CRS and VRS the non-parametric Data Envelopment Analysis (DEA) by investigating the 40 Indian commercial banks from the 2004 to 2013. The study period contains two years of the global financial crisis period that can help us understand whether the financial crisis has the effect on the Indian banking system or not. Our study finds that the Indian banking industry seems not be influenced by the crisis, and almost efficiency scores are shows an upward tendency during the 2004 to 2013. The average efficiency scores of the cost efficiency, allocative efficiency, technical efficiency, pure technical efficiency, and scale efficiency are 0.652, 0.762, 0.843, 0.919 and 0,917 respectively by using both CRS, VRS DEA model. In order to establish a relationship among the market structure hypothesis and efficiency structure hypothesis and profitability, the panel regression are employed, besides, we use the Hasman test to decide to which effect model is more appropriate (Random effect model or fixed effect model). The result looks interesting, because all four hypotheses, namely, Structure Conduct Performance (SCP), Relative Market Power (RMP), Relative Efficiency Hypothesis (RES) and Scale Efficiency Hypothesis (SES), are not hold in the Indian banking system. Therefore, we decompose the x-efficiency into technical efficiency and allocative efficiency to run the panel regression in order to look insight into the result.